2016
DOI: 10.1007/s11252-016-0621-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends in bird species richness, abundance and biomass along a tropical urbanization gradient

Abstract: AcknowledgementsWe thank Lilian Twanza and Osman Mwebe, who also took part in some of the bird counts in Kampala, and to NatureUganda for data from the rural sites. We are also grateful to L. Bennun, J. Roberts, P. Robinson and J. Pierini for providing personal observations on scavenger populations in African cities, and to an anonymous referee whose constructive comments improved the manuscript. 3Abstract Impacts of urbanization on biodiversity are commonly studied using urbanization gradients which provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
(52 reference statements)
2
30
1
Order By: Relevance
“…We observed a decline in species richness across the rural‐to‐urban gradient, a relationship that has been observed across numerous biogeographic regions (reviewed in Marzluff , Chamberlain et al. ). Several studies have documented a peak in species richness at intermediate portions of the rural‐to‐urban gradient, a pattern expected under the intermediate disturbance hypothesis (e.g., Blair , Blair and Johnson , reviewed in Marzluff ).…”
Section: Discussionsupporting
confidence: 68%
“…We observed a decline in species richness across the rural‐to‐urban gradient, a relationship that has been observed across numerous biogeographic regions (reviewed in Marzluff , Chamberlain et al. ). Several studies have documented a peak in species richness at intermediate portions of the rural‐to‐urban gradient, a pattern expected under the intermediate disturbance hypothesis (e.g., Blair , Blair and Johnson , reviewed in Marzluff ).…”
Section: Discussionsupporting
confidence: 68%
“…We retrieved a total of 114 publications after filtering out those outside our research focus. It was evident that the most frequent response to urbanization was negative (84% of publications; e.g., Clergeau et al, 1998;Palomino and Carrascal, 2005;Lepczyk et al, 2008;MacGregor-Fors and Schondube, 2012;Chamberlain et al, 2017;Sol et al, 2017), few studies reported no clear relationships (8% of studies; e.g., Merenlender et al, 1998;Fraterrigo and Wiens, 2005;Sorace and Gustin, 2008;Suhonen et al, 2009;Meffert and Dziock, 2013), as well as higher species richness at intermediate levels of urbanization (6%; i.e., JokimĂ€ki and Suhonen, 1993;Blair, 1996Blair, , 1999Blair, , 2004Clucas and Marzluff, 2015;Battisti and Fanelli, 2016;GuettĂ© et al, 2017), and even positive responses to urbanization (2%; i.e., Leveau and Leveau, 2005;Coetzee and Chown, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have commonly observed lower species richness in urban areas relative to that of the surrounding rural landscapes (Clergeau, Croci, Jokim€ aki, Kaisanlahti-Jokim€ aki, & Dinetti, 2006;Sandstr€ om, Angelstam, & Mikusinski, 2006). However, these patterns are by no means universal, and other studies have found a non-linear response, in which areas with intermediate levels of urbanization exhibit the highest richness (Blair, 1996;Marzluff, 2001;McKinney, 2002;Tratalos et al, 2007), whilst overall bird abundance often increases from rural to urban areas (Chace & Walsh, 2006;Faeth, Bang, & Saari, 2011;Njorge, NdaNg'ang'a, & Natuhara, 2014) although other studies have found no trend (Chamberlain, Kibuule, Skeen, & Pomeroy, 2017) or inconsistent responses across different cities (Garaffa, Filloy, & Bellocq, 2009;Jokim€ aki, Clergeau, & Kaisanlahti-Jokim€ aki, 2002).…”
mentioning
confidence: 99%